Procedural justice and relational theory: empirical, philosophical, and legal perspectives - Meyerson, Denise; Mackenzie, Catriona; Mac Dermott, Therese (Routledge research in legal philosophy, 2021)
Introduction : procedural justice in law, psychology, and philosophy / Denise Meyerson, Catriona Mackenzie, and Therese MacDermott -- The empirical study of procedural justice policing in Australia : highlights and challenges / Kristina Murphy -- Procedural fairness and jury satisfaction : an analysis of relational dimensions / Jane Goodman-Delahunty, David Tait and Natalie Martschuk -- Procedural justice in corrections / Julie Barkworth -- Procedural justice, legitimacy and social contexts / Anthony Bottoms and Justice Tankebe -- Procedure-content interaction in attitudes to law and in the value of the rule of law : an empirical and philosophical collaboration / Noam Gur and Jonathan Jackson -- Legal legitimacy and the relevance of participatory procedures / Sarah Sorial -- The inadequacy of instrumentalist theories of procedural justice / Denise Meyerson -- The many facets of procedural justice in legal proceedings / Emanuela Ceva -- Procedural justice, relational equalityand self-respect / Catriona Mackenzie -- Racial profiling as pejorative discrimination / Natalie Stoljar -- Administrative discretion and governing relationships : situating procedural fairness / Kristen Rundle -- The framing of tribunal procedures : a question of balance or a participation-centred approach? / Therese MacDermott.